Analysis of Factors Affecting Traders' Income on Traditional Markets in Indonesia - Herman (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2021)
This study aims to determine the analysis of the factors that influence traders in the Panam-Pekanbaru Traditional Market, Indonesia. The sample in this study were 61 traders. Data collection techniques using a questionnaire. The data analysis method used SPSS version 25. Finding showed that partially the variables that had a significant effect were working hours and capital, while the non-significant variable was length of business. While the results of the research simultaneously that all independent variables have a positive effect on the dependent variable.